The position of English in secondary schools in ex-industrial communities of the East Midlands of England - Perry, John (2024)
This thesis explores the position of English in ten secondary school located in ex-industrial communities of the East Midlands of England. The research is situated in a context of national education reforms, seen by some to promote a problematic version of English based on inappropriate epistemological foundations, lacking the subject’s wider potential as a socially just discipline; since the introduction of the reforms, English has become increasingly unpopular in schools. This thesis challenges system-level policies by exploring how influential teachers position English in the contexts of their schools.